Aggravated Uncertainties, Researcher Resilience, and Ambiguous Positionality Doing Fieldwork in China Amid COVID-19 Pandemic - Hongsheng Zhao; Wenwei Bao (International Journal of Qualitative Methods)
This paper aims to answer the research questions of ‘How did COVID-19 aggravate the uncertainties in geographical fieldwork, and how could the researchers cope with the challenges?’ Referring to the case study method in scrutinising a fieldwork case that has been conducted by the researchers on Chinese rural-urban migrants in 2020–2021, this research explores the multi-layers of increased uncertainties amid COVID-19. It reveals that that recent COVID-19 pandemic and its knocking-on effects have profound impacts on fieldwork in Chinese context: not only aggravating the scale of uncertainties, but also extending the uncertainties through several dimensions, including harder access to the field, more severe surveillance, which lead to fragile trust between informants and field researcher. The article further posits the significance of researcher’s resilience and reflectivity in fieldwork to address the emerging challenges, proposing adjusted positionality for researchers under the similar context of doing fieldwork in China amid COVID-19 pandemic.